Thomas Nast : political cartoonist - Vinson, John Chalmers (University of Georgia Press, 2014)
Included in this book are more than 150 examples of Nast's work which, together with the author's commentary, recreate the life and pattern of artistic development of the man who made the political cartoon a respected and powerful journalistic form.